Dominion Atlantic Railway Line building, ca. 1906 - Goodrich, E.W. (Tufts Archival Research Center, 2005)
Elevated view of the Dominion Atlantic Railway Steamship Line building, located at the far east end of Long Wharf. Signage painted on the west-facing facade indicates both the section and storage divisions within the building, as well as the location of the U.S. Immigration Office and the Service and Passenger Entrance. Smokestacks of a docked steamship are seen behind or to the east of the building. Cargo containers and boxes are piled both within the storage areas found on both the first level and in front of the Dominion Atlantic building. Men can be seen among the cargo piles. Horse-drawn wagons, some loaded with cargo, wait in front of the building. A flag pole is located on top of the Dominion Atlantic building, its flag unfurled and blowing in the wind. Lantern slide number: 41 2 15/16 x 2 1/2, 4 x 3 1/4 overall Lantern slides